Association between Charlson Comorbidity Index and in-hospital outcomes among aortic stenosis patients undergoing aortic valve replacement: an observational study at the National Clinical Research Center for Cardiovascular Diseases - Shaoping Nie; Xiao Wang; Xin Huang; Wen Zheng; Min Suo; Xuedong Zhao (BMJ Open)
Objectives This study aimed to evaluate the impact of the Charlson Comorbidity Index (CCI) on in-hospital outcomes in patients with aortic stenosis (AS) undergoing aortic valve replacement (AVR) and to compare the efficacy of transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR) in patients with different comorbidity burdens.Setting The National Clinical Research Center for Cardiovascular Diseases.Participants A retrospective analysis was conducted on 3380 AS patients who underwent AVR in Beijing Anzhen Hospital from January 2015 to October 2021.Interventions Patients were stratified into low (0–1) and high (≥2) CCI groups.Primary and secondary outcome measures The primary outcome was Valve Academic Research Consortium-2 (VARC-2) composite early safety endpoints.Results Patients with high CCI scores exhibited significantly higher rates of VARC-2 composite adverse outcomes compared with those with low scores (50.3% vs 44.2%, p=0.001). After adjusting for confounding factors, high CCI scores were independently associated with the VARC-2 composite adverse outcomes (OR=1.36, 95% CI 1.17 to 1.58, p<0.001). In patients aged ≥65 years, TAVR demonstrated lower composite event rates compared with SAVR, regardless of CCI score (low CCI: 17.6% vs 54.3%, p<0.001; high CCI: 33.7% vs 62.8%, p<0.001).Conclusions CCI is a significant predictor of in-hospital composite adverse events in AS patients undergoing AVR. TAVR may be preferred over SAVR for patients aged ≥65 years, irrespective of comorbidity burden, to minimise composite events risk. These findings underscore the importance of considering comorbidity burden in treatment decision-making for AS patients.Trial registration number NCT05797402.